A süllyedő falu - Szirmai, Márton (Hungary : Pálos, György, 2007)
The Hungarian village of Medgyesbodzás is slowly sinking, and the inhabitants are baffled. The village receives very little help from the national authorities, so they turn to the European Union. The middle-aged József does his best to learn English, so when they file a request for EU assistance, he can submit a short film in which he and the other villagers tell their story. But in the meantime, young people are moving away from the village and a solution seems farther away than ever. Moreover, the reason why the village is sinking is not clear either. Medgyesbodzás thus becomes a symbol of the Hungarian rural areas in this humorous and provocative short.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films